Piezoelectric inkjet coating of injection moulded, reservoir-tipped microneedle arrays for transdermal delivery. (4th June 2019) - O'Mahony, Conor; Bocchino, Andrea; Haslinger, Michael J; Brandstätter, Stefan; Außerhuber, Helene; Schossleitner, Klaudia; Clover, A James P; Fechtig, Daniel
Abstract: Coated microneedles have significant potential for use in transdermal delivery applications. In this paper, we describe the fabrication of microneedle master templates using microstereolithography techniques and subsequently use a commercial injection moulding process to replicate these microneedles in biocompatible cyclic olefin polymer (COP) materials. Notably, the 475 μ m-tall needle designs feature a shallow pit or reservoir at the tip, thereby providing both a target and holder for incoming droplets that are deposited using a piezoelectric inkjet printer. Using this design, no tilting or rotation of the needle array is required during the filling process. In the preliminary tests reported here, the reservoir is filled with a FITC-labelled dye that acts as a model drug, and ex vivo skin tests are used to verify skin penetration, the transfer of this model drug to the skin and to measure the reliability of the needles themselves. To our knowledge, this is the first time that such an inkjet-filled, reservoir-tipped microneedle has been demonstrated.